EFFECTS OF STARCH-GLYCEROL CONCENTRATION RATIO ON MECHANICAL AND THERMAL PROPERTIES OF CASSAVA STARCH-BASED BIOPLASTICS - Akbar Hanif Dawam Abdullah; Oceu Dwi Putri; Winda Windi Sugandi (Jurnal Sains Materi Indonesia, 2019)
This study aimed to investigate the effects of different starch-glycerol concentration ratio on mechanical and thermal properties of cassava starch bioplastics. Bioplastics were prepared by mixing starch with glycerol at different starch-glycerol w/w ratio (2.5:1, 2.75:1, 3:1 and 3.5:1). Mechanical properties was evaluated by measuring tensile strength and elongation at break where thermal properties was assessed by thermogravimetric analysis to determine the glass transition temperature (Tg), melting temperature (Tm) and melting enthalpy (ΔHm) of bioplastics. Microstructure and chemical interactions in bioplastics were evaluated by SEM and FTIR. The surface hydrophobicity was determined by measuring the water contact angle. The increase of starch-glycerol concentration in bioplastics formed rough surface where the interaction of glycerol and starch molecules mainly occurred through hydrogen bonds. It also formed stronger and more rigid structure with the increase in tensile strength from 1.90 MPa to 2.47 MPa and the decrease in elongation at break from 8.55% to 5.92%. Furthermore, the increase of starch-glycerol concentration increased Tg from 37.5 ºC to 38.6 ºC, Tm from 96.3 ºC to 120.7 ºC and ΔHm from 100.4 J/g to 155 J/g. Moreover, surface contact angle of bioplastics was increased from 40.6º to 60.2º with the increase of starch-glycerol concentration ratio.